Novel Approach for Evaluating Video Transmission using Combined Scalable Video Coding over Wireless Broadband Network - Kalvein Rantelobo; Kalamullah Ramli; Wirawan Wirawan (Institute of Advanced Engineering and Science, 2018)
One of the main problems in video transmission is the bandwidth fluctuation in wireless channel. Therefore, there is an urgent need to find an efficient bandwidth utilization and method. This research utilizes the Combined Scalable Video Coding (CSVC) which comes from Joint Scalable Video Model (JSVM). In the combined scalable video coding, we implement Coarse Grain Scalability (CGS) and Medium Grain Scalability (MGS). We propose a new scheme in which it can be implemented on Network Simulator II (NS-2) over wireless broadband network. The advantages of this new scheme over the other schemes are more realistic and based on open source program. The result shows that CSVC implementation on MGS mode outperforms CGS mode.